Performance analysis of tetraploid striped catfish (Pangasianodon hypophthalmus) resulting from heat shock induction - Hartami, Prama; Carman, Odang; Alimuddin, Alimuddin; Jr, Muhammad Zairin; Rahman, Rahman; Hermawan, Dede (Acta Aquatica: Aquatic Sciences Journal, 2021)
Striped catfish tetraploid induction through heat shock that carried out in this study is not intended to produce on growth fries.But to form a broodstock to produce triploid on growth fries through cross breeding without any physical shock induction process.The fries from the heat shock induction in the previous study were screened or selected by observing the maximum number of nucleoli in fin cells.The number of tetraploid individuals used in the performance test was 105 which were placed in three different concrete tanks.The results showed that the growth of tetraploid striped catfish was more significant than diploid with a difference in the daily weight percentage about 0.497% and 0.158% for length but insignificant differences in FCR and SR.In gonadal development based on histological observations, it was shown that each tetraploid and diploid both male and female striped catfish were at the same level of gonadal maturity.Female gonads were at the previtellogenic oocytes and vitellogenic oocytes, but males are dominated at the stage of spermatocytes and spermatozoa.This histology also shows us that the female gonad was still at the development stage, while the male had entered the mature stage and ready to be spawned.